Marine Shells of Glycymeris spp. from the Late Upper Palaeolithic of the Eastern Adriatic –a Contribution to Archaeomalacological Research (Archaeologia Adriatica, 2025)
Malacological remains are commonly found at archaeological sites and include both complete and fragmented shells of gastropods, bivalves and scaphopods. Archaeomalacology, the discipline dedicated to studying such remains, offers valuable insights into various aspects of prehistoric life – including economy, subsistence, social practices, and symbolic behaviour. Recent research has highlighted the multifaceted roles of marine shells since the Lower Palaeolithic, when they were used as ornaments, tools, containers and vessels. Among the species that stand out due to their functional diversity, shells of the genus Glycymeris are particularly prominent. In previous studies of prehistoric sites in the Eastern Adriatic, Glycymeris specimens have most often been interpreted as personal ornaments, while their potential utilitarian functions have remained largely unexplored. This paper presents a systematic review of Glycymeris spp. specimens from the Late Upper Palaeolithic of the Eastern Adriatic, synthesising available data on their archaeological context, state of preservation, and morphological characteristics. By comparing these finds with recent research on the function and role of marine shells in prehistoric contexts, the study emphasises the diversity of possible interpretations and underscores the need for future functional analyses that could shed light on the diverse roles of Glycymeris shells among Late Upper Palaeolithic populations in the Eastern Adriatic.
Keywords: Archaeomalacology; Glycymeris spp.; Late Upper Palaeolithic; Eastern Adriatic